Top Executive Pay: Tournament or Teamwork? - O'Reilly, Charles A.; Wade, James (Journal of Labor Economics, 1993)
Tournament mechanisms suggest the need for ever larger rewards to motivate those at the highest organizational levels. But arguments for the efficiency of executive pay compression have also been made. This study reports the results of an empirical investigation of executive compensation using over two-hundred firms and in excess of two thousand executives per year over a five-year period. Results are consistent with the operation of tournaments but fail to find support for the empirical importance of considerations of pay equity at the top of corporations. Copyright 1993 by University of Chicago Press.